The size of the weak bosons - Fritzsch, Harald. (2013)
We study the hypothesis that the bosons are composite systems, which have a size of the order of 10−17 cm. The electromagnetic self-energies of the weak bosons lead to specific departures from the standard elektroweak model, in agreement with observation. Above the energy of 1 TeV the standard electroweak model breaks down completely.